The Limits of the "Progressive" Institutional Change: Migration and Remittances Experiences. Issue 2 (2nd April 2020) - Correa, Eugenia; Girón, Alicia
Abstract: The financial and business expansion towards both sides of the Mexico-U.S. border, what could be called the financial diaspora that accompanies Mexican´s migration to the United States and U.S. Corporations to Mexico, has been a process full of nuances and components with different characteristics. Beyond the governments and their migratory and investment policies, the characteristics of the different migrant groups and corporations, the cultural gaps, and the "progressive" institutional changes are subject to a dynamic of survival-assimilation-earnings. Even when powerful trials of organization are observed, a strong and imminent current of regressive institutional change (Veblen) has been gaining space. This article is circumscribed to analyze some key aspects of the financial behavior Mexican migrants to the United States, who have become entrepreneurs, have had. Their enormous limitations of financing are exposed, including the different stages to access credit to the businesses of residents in Mexico and to Mexican businesspeople abroad. The article contends the transformation in financing on both sides of the border has been decisive.